Effects of Cooperative Learning Strategy on Enhancing EFL Tertiary Students' Writing Skills - Lhmady, Jauda Jafar; Al-Jaro , Morshed (BRU ELT JOURNAL, 2023)
The study aimed to examine the effect of co-operative learning on developing EFL tertiary students’ writing skills. Forty-one EFL students at a public university in Yemen were selected to participate in this study. They were taught writing through the traditional method of teaching adopted by the teachers in the college for a month and a half. Then they were taught writing through using co-operative learning strategy for another month and a half. Three pre-tests and three post-tests as well as attitudinal questionnaire were used to collect the data of the study. The study employed descriptive statistics, inferential analysis as well as the effect size to determine the effect of co-operative learning on developing the students' writing skill. The results of the tests revealed that the students' scores of the post-tests after using the co-operative learning strategy were significantly better than their scores of the pre-tests after using the traditional method. The results of the questionnaire responses showed that the students’ attitudes towards co-operative learning were positive. The study has come up with some recommendations for educators and for future researches concerning the issue in question.